Assessment of divine proportion in the cranial structure of individuals with Angle Class II malocclusion on lateral cephalograms - Silva, Marcos André dos Santos da; Medici Filho, Edmundo [UNESP]; Castilho, Julio Cezar de Melo [UNESP]; Gil, Cássia T. Lopes de Alcântara (Dental Press International, 2012)
INTRODUCTION: The study of the Divine Proportion (Φ = 1.618) began with the Greeks, having as main researchers the mathematician Pythagoras and the sculptor Phidias. In Dentistry, Ricketts (1981-82) was an early to study this issue. OBJECTIVE: This study proposed to evaluate how some cephalometric measures are presented in relation to the Divine Proportion, with the total of 52 proportions, formed by 28 cephalometric landmarks. METHODS: Lateral cephalograms of 40 Class II adults patients aging from 17 to 45 years (13 male and 27 female) were evaluated. The linear distances between the landmarks were measured using Radiocef Studio software. RESULTS: After statistical analysis, the data shown an average of 65,48% in the Divine Proportion, 17,5% in the relation Ans-Op/V1S-DM16 and 97,5% in the relations Na-Me/Na-PoNa e Na-PoNa/Na-Gn. CONCLUSION: Among all cephalometric measurements investigated, the lower facial third and the dental arches showed the smallest percentages of Divine Proportion.
Keywords: Divine Proportion; Class II malocclusion; Cephalometry